1999
DOI: 10.1097/00005768-199910000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic factors associated with Achilles tendinitis in runners

Abstract: A combined discriminant analysis using the above mentioned significant variables revealed that plantar flexion peak torque, touchdown angle, and years running were the strongest discriminators between runners afflicted with Achilles tendinitis and runners who had no history of overuse injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
2
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(198 citation statements)
references
References 20 publications
11
177
2
8
Order By: Relevance
“…60 Decreased Plantar Flexion Strength Decreased plantar flexion strength has been associated with Achilles pathology. 79,86,118 McCrory et al 86 noted a 4-Nm difference in isokinetic plantar flexion strength when comparing the strength of a healthy group of runners to the unaffected ankle in a group of injured runners. While statistically significant, it is unlikely that a 4 Nm difference is clinically important.…”
Section: Abnormal Subtalar Range Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…60 Decreased Plantar Flexion Strength Decreased plantar flexion strength has been associated with Achilles pathology. 79,86,118 McCrory et al 86 noted a 4-Nm difference in isokinetic plantar flexion strength when comparing the strength of a healthy group of runners to the unaffected ankle in a group of injured runners. While statistically significant, it is unlikely that a 4 Nm difference is clinically important.…”
Section: Abnormal Subtalar Range Of Motionmentioning
confidence: 99%
“…As it relates to pronation, comparing a healthy (n = 58) and injured group of runners with Achilles tendinopathy (n = 31), McCrory et al 86 identified that the injured group had more calcaneal inversion at initial contact, displayed greater pronation, and took less time to achieve maximal pronation. Likewise, other work has identified a significant relationship between Achilles tendinopathy and a forefoot varus structural abnormality.…”
Section: Pronationmentioning
confidence: 99%
See 1 more Smart Citation
“…The various predisposing risk factors related to Achilles tendinopathy that are suggested as being important in the literature are listed in Table 2 (Clement et al, 1984, Lysholm and Wiklander, 1987, Hess et al, 1989, Kvist, 1991, Haglund-Åkerlind and Eriksson, 1993, Kvist, 1994, DeMaio et al, 1995, Kannus, 1997a, Alfredson et al, 1998a, Kaufman et al, 1999, McCrory et al, 1999, van der Linden et al, 1999, Järvinen et al, 2001, Kader et al, 2002, Paavola et al, 2002a, Khaliq and Zhanel, 2003, Järvinen et al, 2005, Mahieu et al, 2005, Alfredson and Öhberg, 2005c. …”
Section: Etiology -Deals With the Causes Or Origins Of Diseasementioning
confidence: 99%
“…Several studies report some kind of malalignment, such as hindfoot inversion, or foot hyperpronation as being related to Achilles tendinopathy (Kvist, 1991, Kaufman et al, 1999, McCrory et al, 1999. Kvist reports that 60% of patients with chronic Achilles tendon disorder had some kind of predisposing malalingment of the lower extremity (Kvist, 1991, Kvist, 1994.…”
Section: Intrinsic Factorsmentioning
confidence: 99%